Realokasi Pegawai Sebagai Salah Satu Upaya Pengembangan Karier - Mulyadi, M. Takdir (Journal the Winners: Economics, Business, Management, and Information System Journal, 2001)
Article clarifies a procedure of staff reallocation with a case study at the agency of Agricultural Research and Dvelopment. It present the idea of reallocation, problems, objectives, methodology, the present staff condition concerning staff composition, research policy, goal target, and its constraints as well as policy and activies to solve them.